2014
DOI: 10.1186/1755-8794-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genome-wide association, coexpression network, and expression single nucleotide polymorphism analysis identifies novel pathway in allergic rhinitis

Abstract: BackgroundAllergic rhinitis is a common disease whose genetic basis is incompletely explained. We report an integrated genomic analysis of allergic rhinitis.MethodsWe performed genome wide association studies (GWAS) of allergic rhinitis in 5633 ethnically diverse North American subjects. Next, we profiled gene expression in disease-relevant tissue (peripheral blood CD4+ lymphocytes) collected from subjects who had been genotyped. We then integrated the GWAS and gene expression data using expression single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 64 publications
2
56
0
1
Order By: Relevance
“…This type of probabilistic causal network structure has previously been demonstrated to represent biologically functional pathways across a broad range of diseases including obesity and diabetes (20, 5153), asthma and COPD (54, 55), and Alzheimer’s disease (56). We next excluded genes previously associated with PD (23), including LRRK2 , as well as genes within 1 Mb of LRRK2 to see whether either LRRK2 or other genes could be “recovered” by the network as being co-expressed with the IBD-associated genes.…”
Section: Methodsmentioning
confidence: 99%
“…This type of probabilistic causal network structure has previously been demonstrated to represent biologically functional pathways across a broad range of diseases including obesity and diabetes (20, 5153), asthma and COPD (54, 55), and Alzheimer’s disease (56). We next excluded genes previously associated with PD (23), including LRRK2 , as well as genes within 1 Mb of LRRK2 to see whether either LRRK2 or other genes could be “recovered” by the network as being co-expressed with the IBD-associated genes.…”
Section: Methodsmentioning
confidence: 99%
“…27 GWAS of ethnically diverse North American subjects identified distinct genome-wide significant loci among Latinos, with integrative genomic analyses showing enrichment of the identified GWAS loci for mitochondrial pathways. 28 …”
Section: Genomementioning
confidence: 99%
“…Gene-based coexpression network analyses together with expression single nucleotide polymorphism (eSNP) provide a powerful framework by pinpointing GWAS loci for eSNPs and mapping these GWAS hit genes to relevant modules/interactome representing disease-driven functional pathways (13,70). Bunyavanich et al (70) report mitochondria module from CD41+ lymphocytes gene expression data, showing an effect of the GWAS hits. In the absence of such genotype data, coexpression network analyses alone can further provide meaningful interactomes of genes associated to asthma symptoms.…”
Section: Systems Biology Approach: Dissecting Complexity Of Asthma Comentioning
confidence: 99%
“…To date, there are several GWAS on allergic rhinitis (70): National Human Genome Research Institute catalogs one GWAS of allergic rhinitis comparing 33 for asthma and 61 diabetes (71), Andiappan et al report no significant GWAS loci for 942 Chinese subject, Ramasamy et al report one genome-wide significant locus in a GWAS meta-analysis of 12,898 Europeans (71), and Hinds et al report 16 genome-wide significant loci for self-reported allergy in a GWAS meta-analysis of subjects of European ancestry (72). To a broader context, Torgerson et al (73) report five asthma-susceptible loci from 5416 individuals in diverse North American population, replicated in additional 12,649 individuals from the same ethnic groups.…”
Section: Multiscale Systems Biology Genome Wide Association Studies: mentioning
confidence: 99%
See 1 more Smart Citation